Frequency analysis of numbers:applications in ergonomics and diagnosis of computer keyboard faults (2011)
"This study explores the potentiality of decimal digits distribution to differentiate between chaotic numbers were obtained using FORTRAN codes. Logistic equation was solved for only parameters (Ks') known to exhibit chaotic behaviour with initial value of 0.3 for all cases. Graphs of decimal digits distributions were made with Microsoft Office Excel 2003.Three hundred and eighty nine (389) seed values used for this study range between 1031 and 9998 while the corresponding Logistic equation parameter (K) used range between 3.570 and 3.999. Numbers (0, 1, 2, 6, 7 and 9) recorded zero frequency at first decimal out of ten (10) thousand chaotic solutions for parameter (K=3.570). Similarly the frequency distribution for the first decimal of the chaotic solution is highly biased in favour of numbers 8, 3, 5 and 4 respectively for parameter (k=3.570). Numbers with zero frequency range between six (6) at very low parameter and one (1) at very high parameter. In sum the first decimal digit of chaotic solution distribute drastically different from near uniform distribution observed for other cases of decimal digits. This study has shown that a biased distribution of first decimal digits of a number set is a strongindication of chaos. In addition the results of this study can be of great advantage in diagnosing some computer keyboard faults and ergonometric problems associated with frequent use of some number keys.Track 1: ErgonomicsfHuman Factors. Track 2:Maintenance "